Filtro ativo de potência paralelo trifásico a quatro fios com otimização do controle preditivo - Bezerra, Thales Martins (2024)
This work presents a Three-Phase Four-Wire Shunt Active Power Filter (SAPF) using Finite Set Model Predictive Control (FCS-MPC) for current and DC-Link voltage control. The objective is to mitigate harmonic distortions, improve power factor, and balance the grid current at the point of coupling. The FCS-MPC strategy is combined with the ThreeDimensional Space Vector Pulse Width Modulation (3D-SVPWM) technique, allowing for a reduction from 16 to 8 tested vectors, resulting in a 43% reduction in processing time. By analyzing the zero component of the grid current, it is possible to reduce to 4 tested vectors, achieving a 67% reduction in processing time. Simulations and experimental results are presented to validate the effectiveness of the proposed strategy, including optimization with sensor reduction and the implementation of SAPF Inductive-Capacitive-Inductive (SAPF LCL) to improve power quality.